2020
DOI: 10.37706/iconz.2020.238
|View full text |Cite
|
Sign up to set email alerts
|

Technology Adoption among Zakat Institutions in Malaysia

Abstract: This research observes technology adoption among zakat institutions in Malaysia. To achieve the said objectives, qualitative methodology approach is adopted in this research where primary data is collected via observation of website or any related materials that support technology application among Zakat institutions in Malaysia which including website, online collection or payment system and others. Findings from the observation indicate that majority of the Zakat institutions have started to utilise technolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…There are more than 440 research papers published covering zakat and technology (Kasri and Yuniar, 2021; Widiastuti et al , 2021; Fauzia, 2020; Budi, 2022; Hassan and Muneeza, 2021; Hudaefi and Beik, 2021; Khatiman et al , 2021; Mohd Nor et al , 2021; Omar and Khairi, 2021; Syahbudi and Moertiono, 2021; Rusydiana and Nailah, 2020; Salleh and Chowdhury, 2020; Sulaeman and Ninglasari, 2020; Muneeza and Nadwi, 2019; Shaari et al , 2019). Muneeza and Nadwi (2019) observed that apart from using online platforms to enhance zakat administration using technology: rice automated teller machines are used to disburse zakat in-kind to the needy recipients; mobile applications are also being used; and blockchain platforms are also being used.…”
Section: Theoretical Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…There are more than 440 research papers published covering zakat and technology (Kasri and Yuniar, 2021; Widiastuti et al , 2021; Fauzia, 2020; Budi, 2022; Hassan and Muneeza, 2021; Hudaefi and Beik, 2021; Khatiman et al , 2021; Mohd Nor et al , 2021; Omar and Khairi, 2021; Syahbudi and Moertiono, 2021; Rusydiana and Nailah, 2020; Salleh and Chowdhury, 2020; Sulaeman and Ninglasari, 2020; Muneeza and Nadwi, 2019; Shaari et al , 2019). Muneeza and Nadwi (2019) observed that apart from using online platforms to enhance zakat administration using technology: rice automated teller machines are used to disburse zakat in-kind to the needy recipients; mobile applications are also being used; and blockchain platforms are also being used.…”
Section: Theoretical Analysismentioning
confidence: 99%
“…Technology can also be used to provide correct information about the zakat authorities in a timely manner to the public, as it is found that one of the reasons why mistrust of the public about zakat authorities exists due to the feeding of wrong information in social media about them (Shaari et al , 2019). Salleh and Chowdhury (2020) also state that the use of technology in zakat administration will increase the trust of the public toward zakat institutions. Likewise, Khatiman et al (2021) also state that blockchain-based zakat collection will overcome the trust issues of zakat payers and the issues identified in this regard include zakat payers not being satisfied with the zakat distribution, and lack of transparency in the zakat management leading to mistrust.…”
Section: Theoretical Analysismentioning
confidence: 99%
“…Technology can also be used to provide correct information about the zakat authorities in a timely manner to the public as it is found that one of the reasons why mistrust of the public about zakat authorities exists because of the feeding of wrong information in social media about them (Shaari et al, 2019). Salleh and Chowdhury (2020) also state that the use of technology in zakat administration will increase the trust of the public toward zakat institutions. Likewise, Khatiman et al (2021) also state that blockchainbased zakat collection will overcome the trust issues of zakat payers, and the issues identified in this regard include zakat payers not being satisfied with the zakat distribution and lack of transparency in the zakat management leading to mistrust.…”
Section: Trust In Ezsmentioning
confidence: 99%
“…The transition to a digital economy is anything but easy, specific, or predictable. Moreover, it is likely revolutionary or disruptive, negatively affecting linked organisational outcomes relating to technological capabilities and behaviours (Salleh & Chowdhury, 2020).…”
Section: Digital Transformationmentioning
confidence: 99%